Translating across Languages and Cultures: A Study of Culture-Specific Terms in Bhattarai’s Muglan - Neupane, Nabaraj (Prithvi Journal of Research and Innovation, 2021)
The article aims to explore and categorize culture-specific terms (CSTs) in Bhattarai’s novel Muglan, investigate and analyze the strategies applied in the translated version, assess the strategies for plausibility and evaluate gaps in translation. The data for the study were collected from Nepali and English versions of the novel. The basic technique for collecting data was the observation, which was done by using a checklist. The selection of the 220 cultural terms from the novel was done by applying a purposive sampling procedure. They were investigated in terms of five categories and seven strategies. The major finding of the research was that the terms, categorized into five types, employed seven strategies. The most frequent strategy was the translation by cultural substitution, followed by loan word (plus explanation), neutral word and general word. The subsequent strategies were translation by paraphrase (related words), paraphrase (unrelated words) and omission. Moreover, not specific but different reasons were found in the selection and use of the strategies. Finally, the study found that cultural references necessitate the use of appropriate strategies for transferring them across languages.